2008
DOI: 10.1542/peds.2007-1583
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Echocardiography for the Diagnosis and Management of Pulmonary Vascular Disease in Young Children With Chronic Lung Disease

Abstract: As used in clinical practice, echocardiography often identifies pulmonary hypertension in young children with chronic lung disease; however, estimates of systolic pulmonary artery pressure were not obtained consistently and were not reliable for determining the severity of pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
270
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(282 citation statements)
references
References 25 publications
7
270
2
1
Order By: Relevance
“…Our results suggest that serial echocardiography may be of limited utility because this modality may substantially underestimate the extent of PH and in no way can help determine PVR or pulmonary blood flow. This finding is consistent with other studies that have shown that echocardiography for assessment of PH in the pediatric population may have variable utility (18). We suggest that closer follow-up, possibly including cardiac catheterization, may be necessary in any patient who deviates from the expected clinical course.…”
Section: Pulmonary Hypertension In Cdhsupporting
confidence: 91%
“…Our results suggest that serial echocardiography may be of limited utility because this modality may substantially underestimate the extent of PH and in no way can help determine PVR or pulmonary blood flow. This finding is consistent with other studies that have shown that echocardiography for assessment of PH in the pediatric population may have variable utility (18). We suggest that closer follow-up, possibly including cardiac catheterization, may be necessary in any patient who deviates from the expected clinical course.…”
Section: Pulmonary Hypertension In Cdhsupporting
confidence: 91%
“…10,33 Although some authors suggest that PH should be confirmed with cardiac catheterization before initiating sildenafil therapy, .95% of our cohort did not undergo catheterization, suggesting that clinicians are relying on echocardiography in the diagnosis of PH. Because of the poor correlation between standard echocardiography and cardiac catheterization, 35 clinicians are left to balance the limitations of echocardiography with the risks associated with cardiac catheterization. 36 Given the difficulties in accurately diagnosing PH and the relatively infrequent nature of BPD-PH in the pediatric population, efforts to promote regionalization of care in this unique subgroup of patients will be an important first step in better characterizing disease phenotype, natural history, and response to sildenafil administration.…”
Section: Discussionmentioning
confidence: 99%
“…1,8 A tricuspid regurgitation jet was measured to calculate estimated right ventricular peak systolic pressure using the Bernoulli equation and then adding the assumed right atrial pressures. 11,12 When a tricuspid regurgitation jet was not visualized, then degree of septal flattening and presence of bidirectional shunting was felt to be consistent with PH. 13 Echocardiographic assessment for PH occurred routinely in infants with BPD, still requiring fractional percentage of inhaled oxygen (FiO 2 ) >0.4 or assisted ventilation by 34 weeks postmenstrual age.…”
Section: Diagnosis Of Phmentioning
confidence: 99%